Hungary : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Hungary. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses backgrounds and recent developments in the economy of Hungary. The Hungarian economy has been growing at a robust pace over the past few years helped by supportive macroeconomic policies, a favorable external environment, and high utilization of European Union (EU) funds. Unemployment declined sharply, amid a continuous rise in labor participation. Inflationary pressures have remained subdued. Better-than-budgeted fiscal performance last year helped reduce the public debt ratio. But 2016 is not going to be very encouraging for Hungarian economy. Growth prospects remain subdued reflecting an adverse business climate. The balance of risks is tilted to the downside.